THE EFFECT OF THE SNOWBALL THROWING LEARNING MODEL ON THE LEARNING OUTCOMES OF PANCASILA EDUCATION OF GRADE V STUDENTS OF UPTD SD NEGERI 122379 PEMATANGSIANTAR - Hotnauli Cristina Simanjuntak; Theresia Monika Siahaan; Nancy Angelia Purba (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the effect of the Snowball Throwing learning model on the learning outcomes of Pancasila Education of fifth-grade students of UPTD SD Negeri 122379 Pematangsiantar. This study was conducted in fifth grade with the number of research subjects being 27 students. This type of research is quantitative research with a pre-experimental design using the One Group Pretest-Posttest design. The data analysis techniques used are the Shapirok-Wilk test as a normality test, the Paired sample t-test as a hypothesis test and the N-Gain test. The results of this study indicate that there is a significant influence on the learning outcomes of Pancasila Education of fifth-grade students using the snowball throwing learning model. The results obtained from the average pretest score of students is 48.70 and the average posttest score is 86.48. Based on data analysis using the t-test, it was obtained that tcount > ttable = 24.158 > 1.706 indicates that the sig value (2-tailed) is 0.00 < 0.05 where H0 is rejected and Ha is accepted, meaning there is a significant difference between the learning outcomes of students who use the snowball throwing learning model and the learning outcomes of Pancasila Education of class V students at UPTD SD Negeri 122379 Pematangsiantar.